Type 2 diabetes is linked to higher physiologic markers of effort during exercise - Huebschmann, Amy G.; Scalzo, Rebecca L.; Yang, Xinyi; Schmiege, Sarah J.; Reusch, Jane E. B.; Dunn, Andrea L.; Chapman, Kristina; Regensteiner, Judith G. (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundPeople with type 2 diabetes (T2D) have lower rates of physical activity (PA) than the general population. This is significant because insufficient PA is linked to cardiovascular morbidity and mortality, particularly in individuals with T2D. Previously, we identified a novel barrier to physical activity: greater perceived effort during exercise in women. Specifically, women with T2D experienced exercise at low-intensity as greater effort than women without T2D at the same low-intensity – based on self-report and objective lactate measurements. A gap in the literature is whether T2D confers greater exercise effort in both sexes and across a range of work rates.ObjectivesOur overarching objective was to address these gaps regarding the influence of T2D and relative work intensity on exercise effort. We hypothesized that T2D status would confer greater effort during exercise across a range of work rates below the aerobic threshold.MethodsThis cross-sectional study enrolled males and post-menopausal females aged 50-75 years. Measures of exercise effort included: 1) heart rate, 2) lactate and 3) self-report of Rating of Perceived Exertion (RPE); each assessment was during the final minute of a 5-minute bout of treadmill exercise. Treadmill exercise was performed at 3 work rates: 1.5 mph, 2.0 mph, and 2.5 mph, respectively. To determine factors influencing effort, separate linear mixed effect models assessed the influence of T2D on each outcome of exercise effort, controlling for work rate intensity relative to peak oxygen consumption (%VO2peak). Models were adjusted for any significant demographic associations between effort and age (years), sex (male/female), baseline physical activity, or average blood glucose levels.ResultsWe enrolled n=19 people with T2D (47.4% female) and n=18 people (55.6% female) with no T2D. In the models adjusted for %VO2peak, T2D status was significantly associated with higher heart rate (p = 0.02) and lactate (p = 0.01), without a significant association with RPE (p = 0.58).DiscussionsAcross a range of low-to-moderate intensity work rates in older, sedentary males and females, a diagnosis of T2D conferred higher objective markers of effort but did not affect RPE. Greater objective effort cannot be fully attributed to impaired fitness, as it persisted despite adjustment for %VO2peak. In order to promote regular exercise and reduce cardiovascular risk for people with T2D, 1) further efforts to understand the mechanistic targets that influence physiologic exercise effort should be sought, and 2) comparison of the effort and tolerability of alternative exercise training prescriptions is warranted.